Modeling evapotranspiration for irrigated crops in Jordan using remotely sensed data - Emar Suifan, Marwan S., author; Shatanawi, Muhammad R., author; Al-Bakri, Jawad T., author; Bali, Khaled M., author; Suleiman, Ayman A., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
A study was conducted in Mafraq, Jordan, between 32°15' and 32°50' north latitude and 36°15' and 36°50' east longitude, to investigate the potential use of remotely sensed data to estimate evapotranspiration (ET). Evapotranspiration values were estimating by integrating high resolution (ASTER) and coarse resolution (MODIS) data in the ALARM model. The first part of the study focused on identifying crop types and developing a relationship between plant canopy height (PH) and Normalized Difference Vegetation Index (NDVI) from ASTER. The second part of the study concentrated on modeling actual ET through the integration of data from the previous stage and from the MODIS satellite with the ALARM model. Field surveys and data collection, from March to October 2005, included 37 farms with a total of 247 plots representing irrigated vegetable crops in the area. The ET was calculated using the ALARM model with input parameters of land surface temperature, leaf area index, surface albedo, view angle, view time from 1-km MODIS data and plant canopy height derived from its empirical relationship with ASTER NDVI. Results showed that ASTER satellite imagery could provide an adequate identification of different irrigated vegetable crops in the study area. The use of estimated PH derived from its relationships with ASTER-NDVI instead of ground measurements was not a significant source of error for estimating ET. The average performance of the ALARM model showed a strong spatial variability from one site to another depending on the individual components of each site (total irrigated area and type of irrigated crops). The calculation approach of ET using the ALARM model with MODIS satellite data and crop parameters from ASTER data can be used to provide spatial distribution of actual ET. Therefore, the calibrated approach from this study could be used as a new tool for estimating ET for the irrigated area of Mafraq and similar irrigated regions in Jordan. The study also demonstrated the importance of radiometric correction for satellite images before using them in similar studies.
SCADA and related technologies
Not digitized by CSUL Digital Services.
Presented at SCADA and related technologies for irrigation district modernization, II: a USCID water management conference held on June 6-9, 2007 in Denver, Colorado.